KEBIJAKAN PENGGUNAAN DRONE DAN IMPLEMENTASI PADA KEMENTERIAN LINGKUNGAN HIDUP DAN KEHUTANAN - Gamin Gamin (Jurnal Analisis Kebijakan Kehutanan, 2021)
There is a lot of literature related to the use of drones, including evidence in the Rawa Tripa-Aceh court, but the implementation of this policy needs to be explored specifically at the Ministry of Environment and Forestry. This study aims to examine this. Data were collected through literature studies, interviews, and observations to be analyzed using a policy implementation framework (Grindle, 1980). The findings of the policy content are: the drone policy has positive benefits for validity and legality, as well as authority, but flying permits have the potential to be negative. The degree of change is quite good even though the registration of drones and drone pilots has not been carried out. In the implementation environment, it was found that the central level was quite responsive even though the work unit had not. Competency improvement has been carried out although it is limited to drone pilots. The drone pilot training materials have not met the certification requirements. Research recommendations are: need coordination in drone operation, need guidelines for using drones, need drone registration and drone pilot certification, need competency development designs for drone users and need additional aeronautical knowledge on drone pilot competency development.